Adherence of patients towards drugs and injections prescribed in a private medical institution in Chennai - Suganthi, S.; Mallika, S. V. (International Journal Of Community Medicine And Public Health, 2019)
Background: The irrational use of drugs has become a potential health hazard in the modern days of medicine. Adherence to medication influences treatment outcome. Patient perceptions and education on medications are important determinants for a good adherence to prescribed drugs. Hence the present study intends to assess the knowledge and attitude of patients towards medications. Methods: A cross sectional study was conducted in urban health training centre of a private medical college in Chennai from January 2017 to February 2017. Taking the prevalence of injection preference as 63% and a non-response rate of 10% the required sample size arrived as 125. After obtaining, written informed consent from the participants data was collected using a pretested semi structured questionnaire statistical analysis was done using statistical software SPSS version 21. Results: Out of 125 participants 66.4% were females and the mean age of the study population was 43 years. 78.4% of the participants consult a doctor for medical advice, 58.4% of the patient demanded for injection. Knowledge of patients towards medications was good among highly educated participants which was statistically significant with a P value of 0.02. Conclusions: The knowledge and attitude towards medication was poor in the present study which in turn led to poor adherence. Directing health education towards people would bring significant behavior changes and also policy makers should emphasize on the rational use of drugs by the patients.